Mechanical property change and precipitate evolution during long-term aging of 1.25Cr-0.5Mo steel - Kim, Myung-Yeon; Chu, Dong-Ju; Lee, Young-Su; Jung, Woo-Sang; Lee, Joonho; Lee, Young-Kook; Shim, Jae-Hyeok (ELSEVIER SCIENCE SA, 2020)
The effect of long-term aging at 550 degrees C on the hardness variation and precipitation evolution of a 1.25Cr-0.5Mo steel with ferrite/pearlite structure was investigated. Also, creep-rupture test of the steel was conducted at 550 degrees C. The hardness value generally decreased with increasing aging time due to the spheroidization of cementite (M3C). Interestingly, the hardness value was almost maintained at the aging time ranging from 1,000 to 5,000 h most likely due to the formation of fine needle-like M2C precipitates in ferrite regions. After 5,000 h of aging, the hardness value again decreased with the decrease in the amount of M3C. X-ray diffraction and transmission electron microscopy indicate that the amounts of M2C and M7C3 increases instead of M3C and some of M7C3 precipitates nucleated at M3C particles, growing at the expense of M 3 C around ferrite/pearlite interfaces. On the whole, the simulated precipitation kinetics of the steel using the MatCalc software well described the precipitation sequence. The creep-rupture strength of the steel drastically decreased especially after 1,600 h of rupture time, although it generally decreased with increasing rupture time. The accelerated dissolution of M3C under creep stress/strain was responsible for the drastic decrease in creep-rupture strength.
Keywords: SUPERIMPOSED CREEP STRESS; FIRED POWER-PLANT; M2C CARBIDES; BEHAVIOR; MICROSTRUCTURE; RESISTANCE; STRENGTH; KINETICS